Expanded carrier screening for monogenic disorders: where are we now?. (27th July 2017) - Chokoshvili, Davit; Vears, Danya; Borry, Pascal
Abstract: Background: Expanded carrier screening (ECS), which can identify carriers of a large number of recessive disorders in the general population, has grown in popularity and is now widely accessible to prospective parents. This article presents a comprehensive overview of the characteristics of currently available ECS tests. Methods: To identify relevant ECS providers, we employed a multi‐step approach, which included online searching, review of the recent literature, and consultations with researchers familiar with the current landscape of ECS. Results: As of January 2017, there were 16 providers of ECS tests: 13 commercial companies, 2 medical hospitals, and 1 academic diagnostic laboratory. We observed drastic differences in the characteristics of ECS tests, with the number of conditions ranging from 41 to 1792. Only three conditions (cystic fibrosis, maple syrup urine disease 1b, and Niemann–Pick disease) were screened for by all providers. Where the same disease gene was included by multiple providers, substantial differences existed in the mutations screened and/or variant interpretation/reporting strategies. Conclusion: Given the importance of carrier screening results in reproductive decision‐making, the observed heterogeneity across ECS panels is concerning. Efforts should be made to ensure that clear and concrete criteria are in place to guide the development of ECS panels. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Expanded carrier screening for reproductive purposes has been available to prospective parents since 2010, primarily through direct‐to‐consumer genetic testing companies. The market of expanded carrier screening is rapidly growing, with more than 200 000 tests being performed annually in the United States alone. What does this study add? This study provides a comprehensive review of the expanded carrier screening tests currently available, focusing on test characteristics such as the number and nature of disorders included and variant interpretation strategies used. Appreciable differences have been identified across providers, with the number of disorders screened for ranging from 41 to 1792. In addition, providers differed considerably in terms of the mutations screened and/or variant interpretation/reporting strategies.